Cardioversion of atrial fibrillation in obese patients: Results from the Cardioversion‐BMI randomized controlled trial. (14th November 2018) - Voskoboinik, Aleksandr; Moskovitch, Jeremy; Plunkett, George; Bloom, Jason; Wong, Geoffrey; Nalliah, Chrishan; Prabhu, Sandeep; Sugumar, Hariharan; Paramasweran, Ramanathan; McLellan, Alex; Ling, Liang‐Han; Goh, Cheng‐Yee; et al.
Abstract: Aims: Obesity is associated with higher electrical cardioversion (ECV) failure in persistent atrial fibrillation (PeAF). For ease‐of‐use, many centers prefer patches over paddles. We assessed the optimum modality and shock vector, as well as the safety and efficacy of the Manual Pressure Augmentation (MPA) technique. Methods: Patients with obesity (BMI ≥ 30) and PeAF undergoing ECV using a biphasic defibrillator were randomized into one of four arms by modality (adhesive patches or handheld paddles) and shock vector (anteroposterior [AP] or anteroapical [AA]). If the first two shocks (100 and 200 J) failed, then patients received a 200‐J shock using the alternative modality (patch or paddle). Shock vector remained unchanged. In an observational substudy, 20 patients with BMI of 35 or more, and who failed ECV at 200 J using both patches/paddles underwent a trial of MPA. Results: In total, 125 patients were randomized between July 2016 and March 2018. First or second shock success was 43 of 63 (68.2%) for patches and 56 of 62 (90.3%) for paddles ( P = 0.002). There were 20 crossovers from patches to paddles (12 of 20 third shock success with paddles) and six crossovers from paddles to patches (three of six third shock success with patches). Paddles successfully cardioverted 68 of 82 patients compared with 46 of 69 using patches (82.9% vs 66.7%; P = 0.02). Shock vector did not influence first or second shock success rates (82.0% AP vs 76.6% AA; P = 0.46). MPA was successful in 16 of 20 (80%) who failed in both (patches/paddles), with 360 J required in six of seven cases. Conclusion: Routine use of adhesive patches at 200 J is inadequate in obesity. Strategies that improve success include the use of paddles, MPA, and escalation to 360 J.